New clinical and molecular evidence linking mutations in ARSG to Usher syndrome type IV. Issue 3 (25th December 2020) - Peter, Virginie G.; Quinodoz, Mathieu; Sadio, Silvia; Held, Sebastian; Rodrigues, Márcia; Soares, Marta; Sousa, Ana Berta; Coutinho Santos, Luisa; Damme, Markus; Rivolta, Carlo
Abstract: In murine and canine animal models, mutations in the Arylsulfatase G gene ( ARSG ) cause a particular lysosomal storage disorder characterized by neurological phenotypes. Recently, two variants in the same gene were found to be associated with an atypical form of Usher syndrome in humans, leading to visual and auditory impairment without the involvement of the central nervous system. In this study, we identified three novel pathogenic variants in ARSG, which segregated recessively with the disease in two families from Portugal. The probands were affected with retinitis pigmentosa and sensorineural hearing loss, generally with an onset of symptoms in their fourth decade of life. Functional experiments showed that these pathogenic variants abolish the sulfatase activity of the Arylsulfatase G enzyme and impede the appropriate lysosomal localization of the protein product, which appears to be retained in the endoplasmic reticulum. Our data enable to definitely confirm that different biallelic variants in ARSG cause a specific deaf‐blindness syndrome, by abolishing the activity of the enzyme it encodes. Abstract : Usher syndrome (USH) is a genetic disease characterized by progressive retinal blindness and hearing impairment. It is classically subdivided in three subtypes, defined mostly by the magnitude and the age of onset of patients' auditory deficit. Recently, an atypical form of this syndrome (type IV), characterized by a late onset of both visual and auditory symptoms, has been described. In this work, we identify three novel pathogenic variants associated with USH type IV in the gene ARSG, encoding the Arylsulfatase G enzyme. By functional experiments we also show that these mutations abolish the sulfatase activity of the protein. In addition, mutant enzymes seem to lose their canonical lysosomal localization and are instead retained in the endoplasmicreticulum.